Implementasi CSR PT X dalam Membangun Ketahanan Pakan Ternak - Agung Setiawan; Maman Suherman (Jurnal Riset Public Relations, 2023)
Abstract. PT X's social responsibility program itself refers to ISO 26000: 2010. Responsibility in the form of a form of concern and donation to national development. In this Corporate Social Responsibility program, issues and problems were found regarding the difficulty of obtaining good quality animal feed in Kertawangi Village, Cisarua District, West Bandung Regency. The research objective was to find out how the implementation process was, the obstacles that occurred, and the reasons for choosing Kertawangi Village, Cisarua District, West Bandung Regency. This study uses a qualitative method with a case study approach. Data collection methods were carried out using interview techniques, observation, literature studies, and documentation studies. The results of this study are: 1) PT X builds animal feed resilience, using four stages of CSR, namely the planning stage (social mapping), implementation (carrying out programs based on social mapping), evaluation (assessment of implemented programs), and reporting (form of responsibility to relevant stakeholders). 2) There were obstacles during the implementation of activities, namely there were technical, non-technical, and planting land obstacles for breeders. 3) PT X implemented the CSR program in Kertawangi Village where both of them experienced difficulties in obtaining good quality animal feed. Abstrak. Program tanggung jawab sosial PT X sendiri mengacu pada ISO 26000:2010. Dalam program Corporate Social Responsibility ini ditemukan isu dan permasalahan mengenai sulitnya mendapatkan pakan ternak yang berkualitas baik di Desa Kertawangi, Kecamatan Cisarua, Kabupaten Bandung Barat. Tujuan penelitian adalah untuk mengetahui bagaimana proses pelaksanaannya, kendala yang terjadi, dan alasan memilih Desa Kertawangi Kecamatan Cisarua Kabupaten Bandung Barat. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Metode pengumpulan data dilakukan dengan menggunakan teknik wawancara, observasi, studi literatur, dan studi dokumentasi. Hasil dari penelitian ini adalah: 1) PT X membangun ketahanan pakan ternak menggunakan empat tahapan CSR yaitu tahap perencanaan (social mapping), implementasi (program berbasis tentang pemetaan sosial), evaluasi (penilaian terhadap program yang dilaksanakan), dan pelaporan (tanggung jawab kepada pemangku kepentingan terkait). 2) Terdapat kendala selama pelaksanaan kegiatan yaitu adanya kendala teknis, non teknis, dan lahan tanam bagi para penangkar. 3) PT X melaksanakan program CSR di Desa Kertawangi di mana keduanya mengalami kesulitan dalam mendapatkan pakan ternak yang berkualitas baik.